“Diseño de una planta industrial de producción y comercialización de yogurt natural a base de leche de cabra en la Quinta la Poderosa, en el cantón Macará provincia de Loja - Cueva Arrobo, Rubí Isabel (2024)
Currently in the Sabiango parish belonging to the Macará canton, province of Loja, there is a high demand for yogurt based on goat's milk, which provides excellent health benefits for those who consume it, therefore, this Titration Work focused on designing a plant industrial production and marketing of natural yogurt based on goat's milk in Quinta la Poderosa, in the Macará canton, province of Loja. An infrastructure was proposed that consisted of optimal equipment, technology and machinery to allow its adaptation. At the same time, concrete data was obtained that allowed the design of this industrial plant, the feasibility and a proposal to satisfy the needs of consumers were determined. To do this, appropriate research methods were used, as well as detailed information on the target segment, tools were used to determine income, costs and feasibility of the project. In the financial study, it was determined that the proposed industrial plant for the production and marketing of yogurt based on goat's milk is profitable, resulting in an estimated income of $40,548.21 US dollars, with a capacity of the industrial plant of yogurt of 110 liters per day, and a final production of 54,211.79 liters per year. It is expected that this work can contribute as a model of new implementation options for an industrial yogurt plant in the Macará canton.